2023
DOI: 10.1136/spcare-2022-004100
|View full text |Cite
|
Sign up to set email alerts
|

Access for Cancer Caregivers to Education and Support for Shared Decision Making (ACCESS) intervention: a cluster cross-over randomised clinical trial

Abstract: ObjectivesThe purpose of this study was to test an intervention named ACCESS (Access for Cancer Caregivers to Education and Support for Shared Decision Making). The intervention uses private Facebook support groups to support and educate caregivers, preparing them to participate in shared decision-making during web-based hospice care plan meetings. The overall hypothesis behind the study was that family caregivers of hospice patients with cancer would experience lower anxiety and depression as a result of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…15 The evidence has found that family caregiver depression can be lessened with participation in a Facebook support group. 9 Likewise, the overwhelming perceptions of social workers in this sample is that Facebook online support groups would be at least somewhat beneficial for hospice caregivers (96%). However, the specifics on how to offer this service are not as clear.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…15 The evidence has found that family caregiver depression can be lessened with participation in a Facebook support group. 9 Likewise, the overwhelming perceptions of social workers in this sample is that Facebook online support groups would be at least somewhat beneficial for hospice caregivers (96%). However, the specifics on how to offer this service are not as clear.…”
Section: Discussionmentioning
confidence: 86%
“…21 Another possibility for corporate hospices would be to offer the service from the corporate or regional office. We know that online Facebook groups reduce family caregiver depression 9 and we know from these data that 96% of social workers believe they are valuable for family members. Therefore, it is important to commit to providing this service as an option for family caregivers, even if the group is not an alternative for every caregiver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One recent RCT found that hospice family caregivers who participated in a private online support group on Facebook experienced statistically significant decreases in depression compared with HFCGs in the usual care control group. 21 Study participants also indicated researchers should consider adapting Ready2Care to conditions commonly encountered in hospice, such as dementia and other illnesses that may result in cognitive impairment, as pain may be undercontrolled in these populations due to caregiver difficulties assessing and managing pain among patients who are nonverbal or who experience other communication challenges, 49 highlighting the unique disease-specific contexts in which hospice caregiving takes place. Importantly, however, study findings suggest that any future changes to the Ready2Care pain education brochure should be made in such a way that its clarity and ease of understanding are retained, particularly given that the average of participants' health literacy scores fell between cut-offs for "marginal" and "adequate" levels, and numerous participants commented positively about the lower literacy level at which the Ready2Care pain education brochure is currently written.…”
mentioning
confidence: 99%